Moisés como quem não sabe falar: um estudo exegético de Ex 4,10-17; 6,10-12.29-30 e da presença desse tema nos Evangelhos - Dantas, José Ancelmo Santos (2020)
In three moments, Moses, in dialogue with the Lord, the God of Israel, presents himself as one who isn´t able to speak. Once he says "not to be a man of words" and that he has "a heavy mouth" and "a heavy tongue" (Ex 4,10), in another moment he declares twice to be an "uncircumcised of lips" (Ex 6.12.20). And this as a prophet-leader who is called by God to "speak to his brother Aaron, to all the heads of the community, and to all the children of Israel" (Ex 34: 31-32). By contrast, however, according to the exodal narrative, Moses even spoke to all of these, and he was neither dumb nor stammering. What, then, does the book of Exodus want to say to its listeners when it presents Moses as one who isn´t able to speak? And what theological reflection accompanies the metaphors "heavy mouth", "heavy tongue" and "uncircumcised of lips"? Moreover, besides investigating Moses, within the traditions belonging to the Pentateuch, as those who isn´t able to speak, the study presented here aims at an intertextuality. The four New Testament Gospels, therefore, make a point of re-embracing the subject originally related to Moses in order to work it now in relation to the disciples of Jesus. The solution, in turn, remains the same: every prophetic leader, mosaic, and/or follower of Jesus is invited to experience the mystery that God and/or the Holy Spirit will be "in his/her mouth and will instruct concerning what he/she should speak" (Ex 4: 12b-c; Mk 13: 11; Mt 10: 19; Lk 12: 12; Jn 14: 26)